The Impact of H.264/AVC on Compression and Non-Destructive Evaluation of Piston Data in Industrial Computed Tomography - Ditter, Alexander; Fey, Dietmar; Schön, Tobias; Luxa, Maik; Gruber, Roland (IST 2013 Proceedings, 2013)
The application of video encoding for the compression of Computed Tomography (CT) based projection images is very promising with respect to a more efficient transmission and storage of this particular type of data. Especially the use of 'off-the-shelf' technologies, such as the H.264/AVC codec, ensures long term support due to its widespread use in the media industry. We present an approach for the application of this standard 8-bit video codec even for 16-bit projection data sets. Based on a benchmark set of 200 pistons, we evaluate its performance in terms of the compression rate relative to the original input data. Furthermore, we compare the detection rate of manufacturing defects in the reconstructed volumes to the state-of-the-art technique without video encoding. For this purpose our benchmark does not only contain the projections of the 200 pistons, but additionally the exact information about location and size of the manufacturing defects of the respective piston. We show that the detection rate based on the video encoded projection data is, up to a certain threshold, as good as without compression. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD3.theimp
Keywords: Compression; industrial computed tomography; non-destructice testing; video encoding